2020
DOI: 10.3390/ijerph17228535
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Innovation Media for Improving Physical Distancing Compliance during the COVID-19 Pandemic: A Quasi-Experiment in Thailand

Abstract: To flatten the curve of COVID-19 infections, with no effective pharmacological interventions or vaccine available in the imminent future, public health responses must continue to rely on non-pharmacological interventions. We developed three innovation media to promote physical distancing compliance (i.e., a fearful picture, a red one-way arrow sign, and a norm-speech sticker). This study aimed to compare physical distancing compliance between our interventions and conventional interventions. Our study was a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…The 6 studies that met the inclusion criteria reported the effect of 14 interventions (and 3 other control interventions) and included over 5531 participants (One study, Hoeben et al, 2021 , did not report the N due to the nature of the observational study design). The studies included randomized controlled trials ( n = 4344; Bos et al, 2020 ; Khoa et al, 2021 ; Lunn et al, 2020 ); non-randomized trials ( n = 1187; Blanken et al, 2020 ; Chutiphimon et al, 2020 ); and a natural experiment ( n = unknown; Hoeben et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 6 studies that met the inclusion criteria reported the effect of 14 interventions (and 3 other control interventions) and included over 5531 participants (One study, Hoeben et al, 2021 , did not report the N due to the nature of the observational study design). The studies included randomized controlled trials ( n = 4344; Bos et al, 2020 ; Khoa et al, 2021 ; Lunn et al, 2020 ); non-randomized trials ( n = 1187; Blanken et al, 2020 ; Chutiphimon et al, 2020 ); and a natural experiment ( n = unknown; Hoeben et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies were based in Europe ( Bos et al, 2020 ; Blanken et al, 2020 ; Hoeben et al, 2021 ; Lunn et al, 2020 ), Asia ( Chutiphimon et al, 2020 ); and North America ( Khoa et al, 2021 ). Data were collected between January and August 2020 (See Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These solutions used at the beginning of the pandemic (March-April in Europe) and during its second wave (October-November in Europe) are concerned bivalent. This is because, on the one hand, they have introduced a partial economic crisis in industries such as aviation, gastronomy, hotel, fitness, events, and culture, but they have also created the conditions for the dynamic development of industries based on Internet communication and forced the development of many companies toward increased online services in all industries (Açikgöz and Günay 2020;Chutiphimon et al 2020;Zhang et al 2020). For example, new applications have been developed and service providers have started selling their services online (e.g., fitness, training, accounting).…”
Section: Introductionmentioning
confidence: 99%